Hubungan Pengetahuan Dan Motivasi Perawat Dengan Kelengkapan Pengisian Early Warning Score (EWS) - Surya Prihatini; Fatimah Azzahrah; Saldi Yusuf; Aulya Kartini Dg Karra; Sarifudin Andi Latif (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
The implementation of the Early Warning Score (EWS) in hospital settings plays a crucial role in the early detection of patient clinical deterioration; however, adherence to its completion varies in practice. This variability is influenced not only by technical aspects but also by individual factors among nurses. This study aimed to analyze the relationship between nurses’ knowledge and motivation and the completeness of Early Warning Score (EWS) documentation at UPT RSUD Labuang Baji, South Sulawesi Province. A quantitative study with a cross-sectional correlational design was employed. The study population consisted of all 45 inpatient nurses, using a total sampling technique. Data were collected using a self-developed questionnaire based on literature review and the National Early Warning Score (NEWS) guidelines, and analyzed using univariate and bivariate analyses with Fisher’s Exact Test at a significance level of 0.05. The results showed that the majority of respondents had good knowledge (97.8%), moderate motivation (71.1%), and good completeness of EWS documentation (93.3%). The bivariate analysis revealed no significant relationship between knowledge and EWS completeness (p=0.787), nor between motivation and EWS completeness (p=0.935). In conclusion, nurses’ knowledge and motivation were not associated with the completeness of EWS documentation, indicating that EWS implementation is more strongly influenced by organizational and system-level factors than individual factors.